THE EFFECTIVENESS OF PREGNANCY EXERCISES IN IMPROVING THE QUALITY OF SLEEP FOR PREGNANT WOMEN - Dwita, Putri; Mulyani, Sri; Meinarisa, Meinarisa (Jurnal Keperawatan Universitas Jambi, 2024)
Background: The quality of sleep in pregnant women is very important for the health of the mother and fetus. The National Sleep Foundation (2007) states that 97.3% of pregnant women in the third trimester always wake up at night. On average, pregnant women wake up 3-11 times at night. The cause of mothers often wake up at night due to frequent urination, cramps in the legs, and the mother's anxiety aboutchildbirth. According to Reichner (2015) sleep pattern disturbances in the first trimester were 13%, in the second trimester 19% and increasedin the final trimester by 66%. The incidence of sleep disorders in pregnant women in Indonesia is quite high, around 64% of pregnant women in Indonesia experience sleep disorders. To overcome this, pregnant women need to do pregnancy exercises regularly and optimally to increase the comfort of pregnant women. The purpose of this study was to determine the effectiveness of pregnancy exercise on the quality of sleep of pregnant women. Methods: This research is a literature study by searching for articles using Google Scholar, search engine Pubmed, Semantic Scholar, andGaruda Portal to find articles according to inclusion and exclusion and then reviewing the articles. There were 11 articles obtained from the screening results. Results: Based on the results of a study of 11 articles, it was found that doing pregnancy exercise with a frequency of frequently or more than once and with a duration according to the ability of pregnant women is more effective in improving the quality of sleep of pregnant women. Conclusion: Pregnancy exercise activities can be one of the efforts that can be done to improve the quality of sleep of pregnant women